2011
DOI: 10.1007/s00464-011-2026-1
|View full text |Cite
|
Sign up to set email alerts
|

The role of short-limb Roux-en-Y reconstruction for failed antireflux surgery: a single-center 5-year experience

Abstract: Short-limb RNY reconstruction is an effective remedial procedure for a subset of patients with failed antireflux surgery, but morbidity is significant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 39 publications
0
13
3
Order By: Relevance
“…However, the complication rate in our study is slightly lower than rates reported in other studies (21%–46%) [1216]. One patient had persistent gastroparesis, dysphagia and GERD, however postoperative endoscopic evaluation did not reveal any targets for intervention.…”
Section: Discussioncontrasting
confidence: 79%
See 2 more Smart Citations
“…However, the complication rate in our study is slightly lower than rates reported in other studies (21%–46%) [1216]. One patient had persistent gastroparesis, dysphagia and GERD, however postoperative endoscopic evaluation did not reveal any targets for intervention.…”
Section: Discussioncontrasting
confidence: 79%
“…This effect was further amplified in our patients with previous Nissen fundoplication, as 42.9% of this subset of patients required an open procedure while only 25% of our patients without a previous Nissen required conversion to open. The rate of conversion to open in this study is higher than other series of patients with RYGB after non-bariatric foregut surgery, with rates ranging between 0% – 33% [1216]. In our population this is likely related to the presence of intraabdominal adhesions, as a higher proportion of patients with previous Nissen fundoplication required extensive enterolysis, compared to patients with non-Nissen foregut surgery.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Additionally in our practice, we prefer to opt for RNY as opposed to a redo fundoplication in patients with the following red-flag signs: (1) having severe scarring that precludes recreation of a fundoplication, (2) multiple previous anti-reflux procedures, (3) presence of pathological tissue requiring gastroesophageal resection, (4) severe esophageal dysmotility, (5) delayed gastric emptying, or (6) short esophagus. 18 Patients having either any one of the first three indications or more than one of the latter indications were considered for a RNY procedure at our institution. We also prefer a RNY as re-operative intervention in morbidly obese patients; however, a subset of patients may be averse to this and go redo fundoplication even with BMI >35.…”
Section: Discussionmentioning
confidence: 99%
“…For those patients in whom fundoplication fails, gastric bypass using Roux-en-Y reconstruction has been utilized, and it has been found to be a safe and effective surgical option, particularly in patients with evidence of biliary reflux. 2,3 Surgical management of refractory GERD with gastric bypass in patients with SCI is not currently reported in the literature, to our knowledge, and there is only one other case of Roux-en-Y gastric bypass (RYGBP) in the literature, which was for treatment of obesity in a male with paraplegia. 4 This report describes a case of a morbidly obese male with tetraplegia who underwent a RYGBP for refractory GERD.…”
Section: Introductionmentioning
confidence: 99%